2011
DOI: 10.5194/acp-11-10031-2011
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric impacts of the 2010 Russian wildfires: integrating modelling and measurements of an extreme air pollution episode in the Moscow region

Abstract: Abstract. Numerous wildfires provoked by an unprecedented intensive heat wave caused continuous episodes of extreme air pollution in several Russian cities and densely populated regions, including the Moscow region. This paper analyzes the evolution of the surface concentrations of CO, PM 10 and ozone over the Moscow region during the 2010 heat wave by integrating available ground based and satellite measurements with results of a mesoscale model. The CHIMERE chemistry transport model is used and modified to i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
237
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(255 citation statements)
references
References 69 publications
11
237
2
Order By: Relevance
“…Since then, numerous new generations of on-line-coupled models have been developed worldwide, such as Multiscale Climate Chemistry Model (MCCM) (Grell et al, 2000), Weather Research and Forecasting-Chemistry (WRF-Chem) (Grell et al, 2005) and Global Environmental Multi-scale-Modeling Air quality and CHemistry (GEM-MACH) (Moran et al, 2010). These models have been widely used for Europe and North America and they found that the interactions between meteorology and chemistry can be significant during strong air pollution episodes (Grell et al, 2011;Konovalov et al, 2011;Wong et al, 2012;Chen et al, 2014;Kong et al, 2015;Liu et al, 2016).…”
Section: Wrf-chem Model Descriptionsmentioning
confidence: 99%
“…Since then, numerous new generations of on-line-coupled models have been developed worldwide, such as Multiscale Climate Chemistry Model (MCCM) (Grell et al, 2000), Weather Research and Forecasting-Chemistry (WRF-Chem) (Grell et al, 2005) and Global Environmental Multi-scale-Modeling Air quality and CHemistry (GEM-MACH) (Moran et al, 2010). These models have been widely used for Europe and North America and they found that the interactions between meteorology and chemistry can be significant during strong air pollution episodes (Grell et al, 2011;Konovalov et al, 2011;Wong et al, 2012;Chen et al, 2014;Kong et al, 2015;Liu et al, 2016).…”
Section: Wrf-chem Model Descriptionsmentioning
confidence: 99%
“…On the other hand, depending of the absorbing characteristics of the aerosols (mineral dust, black carbon …) they could energize convective clouds and thus increasing precipitation (Levin and Brenguier, 2009). Feedback effects can be particularly important during strong particles episodes (Konovalov et al, 2011;Chen et al, 2014;Wong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The model documentation and the source code can be downloaded from the CHIMERE website [33]. CHIMERE was successfully used in a number of studies, including those dedicated to investigations of atmospheric effects of wildfires (e.g., [19,21,34,35]). …”
Section: Simulation Datamentioning
confidence: 99%
“…Fire emissions were calculated and introduced into CHIMERE by using the emission model that had been successfully used and described in detail earlier [19,21,36]. Briefly, it assumes that the BB emission rate, E s , of a species, s, in a given grid cell of the horizontal domain in an hour, t, is proportional to the daily mean FRP values, Фd, that were inferred from daily maximum FRP values derived from the MODIS measurements (see Section 2.1.1) for a given grid cell:…”
Section: Simulation Datamentioning
confidence: 99%
See 1 more Smart Citation